Establishment, immunological analysis, and drug prediction of a prognostic signature of ovarian cancer related to histone acetylation - Fang, Yujie; Zhao, Jing; Guo, Xu; Dai, Yunfeng; Zhang, Hao; Yin, Fanxin; Zhang, Xiaoxu; Sun, Chenxi; Han, Zequan; Wang, Hecheng; Han, Yanshuo (Frontiers in Pharmacology, 2022)
In recent years, epigenetic modification has been increasingly regarded as an important hallmark of cancer. Histone acetylation, as an important part of epigenetics, plays a key role in the progress, treatment and prognosis of many cancers. In this study, based on TCGA database, we performed LASSO regression and Cox algorithm to establish a prognostic signature of ovarian cancer associated with histone acetylation modulator genes and verified it externally in GEO database. Subsequently, we performed immunological bioinformatics analysis of the model from multiple perspectives using CIBERSORT algorithm, ESTIMATE algorithm and TIDE algorithm to verify the accuracy of the model. Based on the prognostic model, we divided ovarian cancer patients into high-risk and low-risk groups and assessed survival and the efficacy of accepting immunosuppressive therapy. In addition, based on the analysis of characteristics of the model, we also screened targeted drugs for high-risk patients, and predicted potential drugs that inhibit platinum resistance through connectivity map method. We ultimately constructed a HAMs-related signature containing 10 histone acetylation modulators, among which HDAC1, HDAC10 and KAT7 can act as independent prognostic factors for ovarian cancer and are related with poor prognosis. In the analysis of the tumor microenvironment, the proportion of the B infiltrating cell and the macrophages was significantly different between the high and low risk groups. And the samples with high risk score had higher tumor purity and lower immune score. In terms of treatment, patients in the high-risk group who received immunotherapy had a higher likelihood of immune escape or rejection and were less likely to respond to platinum/paclitaxel therapy. Finally, we screened 20 potential drugs that could target the model for reference.